Pengaruh crowdsourcing dan representasi koleksi terhadap kredibilitas informasi pada museum di Indonesia - Edi Wibowo; Tamara Adriani Salim (Berkala Ilmu Perpustakaan dan Informasi, 2024)
Introduction. This research analyzes the influence of crowdsourcing and representation on the credibility of museum information in Indonesia. The aim of the research is to identify the effect of crowdsourcing on credibility, the effect of representation on credibility, the effect of crowdsourcing and representation on credibility. Data Collection Methods. This research used a quantitative approach to test the relationship between three variables, namely the crowdsourcing variable (X1) and representation (X2) and the credibility variable (Y). The data collection method used a questionnaire distributed to museum managers who have implemented the crowdsourcing concept. Data Analysis. The research results were processed using SPSS v26. Analysis models used were Descriptive Analysis, Classic Assumption Test, Regression Test, Correlation T Test, F Test, and Coefficient of Determination. Results and Discussion. The research results show: 1) crowdsourcing has a positive effect on credibility. 2) representation has a positive effect on credibility. 3) crowdsourcing and representation have a positive effect on credibility Conclusion. The three variables have a significant influence on each other. Crowdsourcing and collection representation influence the credibility of museum collection information in Indonesia.